Research papers : the 12th international Arab conference on information technology : ACIT 2011 (Naif Arab University for Security Sciences, 2011)
"The papers represented reflect the distinctive contributions of multiple intelligentsia -- researchers, engineers, technical professionals and academicians. Together, they represent both government and non-government organizations -- research and academic. The present publication is a pioneer work on Information Technology."--Foreword
"ACIT 2011, Naif Arab University for Security Sciences, 11-14 December 2011."
Keywords: Computer networks -- Arab countries -- Congresses; Electronic commerce -- Arab countries -- Congresses; Information services -- Arab countries -- Congresses; Information technology -- Arab countries -- Congresses; Information technology -- Saudi Arabia -- Congresses